Development and validation of proactive coping smoking cessation in adolescents - Wini Hadiyani; Nisha Nambiar; Faridah binti Mohd Said; Linlin Lindayani; Windy Rakhmawati; Neti Juniarti (International Journal of Public Health Science (IJPHS), 2023)
Smoking is one of the most significant lifestyle factors contributing to the global disease burden. Individuals who use proactive coping will improve their environment and life rather than reacting to the past and planning for the future by constructing and pooling available resources to deal with stressors. However, instruments measured proactive coping toward smoking cessation are limited. This study aimed to develop and test the validity and reliability of proactive coping toward smoking cessation in adolescents. The data collection process was divided into two phases, namely instrument development and psychometric testing. Exploratory factor analysis and reliability testing were conducted on 300 adolescents. Proactive coping smoking cessation (PCSC) is the development of proactive coping inventory (PCI). Loading factor coefficient on support seeking 0.54-0.82, reflective coping 0.585-0.823, strategic planning 0.580-0.736, proactive coping 0.439-0.648, avoidance 0.586-0.826 and preventive coping 0.507-0.707. Cronbach's alpha for PCSC ranged from 0.970 to 0.972. PCSC shows the acceptable internal and external consistency and the results of the exploratory factor analysis (EFA) verify that the six-factor model correctly represents the original PCI factor structure. Future studies are required to test the instrument in different setting and culture.